Diagnostic value of NIPT assay for fetal aneuploidy screening in pregnant women with moderate risk of trisomy in first stage screening - Fatemeh Lalooha; Shokouh Sadat Haji Seyed Abotorabi; Farideh Movahed; Farzaneh Bahrami; Abolfazl Heidari; Monirsadat Mirzadeh (Mashhad University of Medical Sciences, 2022)
Introduction: Aneuploidies are of the most important fetal abnormalities. Diagnostic value and efficacy of NIPT assay in the groups with abnormal results for first trimester combined screening test is not well defined. Therefore, this study was performed aimed to survey the sensitivity and specificity of NIPT for aneuploidies diagnosis in women with moderate risk for trisomy at first trimester combined screening test. Methods: This prospective cohort study was performed in 2017-2018 on 447 women with singleton pregnancy and gestational age of 11 to 13 weeks and 6 days who had moderate risk for trisomy. NIPT analysis was done in all women with moderate risk (1/250 to 1/1500) and was compared with the results from karyotype and phenotype analysis in neonates. NIPT diagnostic accuracy for chromosomal abnormalities was calculated. Data were analyzed using SPSS statistical software (version 22). Results: Two cases with trisomy 21 (0.06%) and one case with trisomy 18 (0.03%) were diagnosed. These three cases were confirmed with amniocentesis and the pregnancy was ended. The neonates' analysis showed normal phenotype results in all of them and NIPT diagnostic accuracy for trisomy 21 and 18 was calculated 100%. Conclusion: In addition to maintain combined screening test benefits, using NIPT is accompanied by high diagnostic accuracy for fetal chromosomal abnormalities assessment.